Heimat und die Einstellung gegenüber Fremden in dem Heimatfilm Grün ist die Heide: Werden alle Fremden gleichgestellt? - Summers, Heidi (Kansas State University, 2021)
This paper examines different aspects of exclusions and belonging in one of the most popular Heimatfilme (homeland films) in Germany during the post-war period in the 1950s. The film Grün ist die Heide (Green is the Heath, 1951) offers an excellent example for analyzing the topic of Heimat often discussed in German literature, specifically how its ideas of home and belonging are not always associated with positive images and happy memories. Heimat can also have negative connotations for some people and those can lead them to be excluded from certain places. In this film, the heath is the home to a community, where newcomers are trying to enter for a number of reasons. Various film characters and scenes will be examined in this study to show the struggle and/or success these newcomers have in trying to accomplish this task. This paper will investigate the reasons for the various outcomes for these newcomers and introduces a new model for acceptance and exclusions of foreigners that is tied to the level of foreignness perceived by the locals. This idea of foreignness in the Heimatfilm has not been investigated much in the existing scholarship and this paper hopes to contribute to a better understanding in this area.
Keywords: Heimat; Gruen ist die Heide; Heimatfilm; Fremd sein